Maintained Physical Activity Induced Changes in Delay Discounting. (July 2017) - Sofis, Michael J.; Carrillo, Ale; Jarmolowicz, David P.
Those who discount the subjective value of delayed rewards less steeply are more likely to engage in physical activity. There is limited research, however, showing whether physical activity can change rates of delay discounting. In a two-experiment series, treatment and maintenance effects of a novel, effort-paced physical activity intervention on delay discounting were evaluated with multiple baseline designs. Using a lap-based method, participants were instructed to exercise at individualized high and low effort levels and to track their own perceived effort. The results suggest that treatment-induced changes in discounting were maintained at follow-up for 13 of 16 participants. In Experiment 2, there were statistically significant group-level improvements in physical activity and delay discounting when comparing baseline with both treatment and maintenance phases. Percentage change in delay discounting was significantly correlated with session attendance and relative pace (min/mile) improvement over the course of the 7-week treatment. Implications for future research are discussed.